Second-Line Antiretroviral Treatment Outcome in HIV-Infected Patients Coinfected with Tuberculosis in Pakistan. (19th April 2023) - Shafiq, Muhammad; Zafar, Sana; Ahmad, Aftab; Kazmi, Abeer; Fatima, Alina; Mujahid, Tanvir Ahmed; Qazi, Rizwan; Akhter, Nasim; Shahzad, Amir; Rehman, Saif Ur; Shereen, Muhammad Adnan; Hyder, Muhammad Zeeshan
Abstract : Background . Tuberculosis (TB) coinfection in human immunodeficiency virus- (HIV-) infected patients is considered a risk of antiretroviral therapy (ART) failure. Coadministration of antitubercular therapy (ATT) with ART is another challenge for TB management. Objective . The study was aimed at investigating contributing factors affecting treatment outcomes in HIV-/TB-coinfected patients. Design . Cross-sectional. Setting . Samples were collected from the Pakistan Institute of Medical Sciences Hospital Islamabad. Subject and Methods . Clinicodemographic and immunovirological factors between the two groups were compared. The Student t -test and chi-square test were applied to compare outcome variables, and logistic regression was applied to determine the effect of TB on virological failure (VF). Main Outcome Measures . TB coinfection did not increase VF even in univariate (p = 0.974 ) and multivariate analysis at 6 and 12 months of 2 nd -line ART start. ARV switching was significant (p = 0.033 ) in TB-coinfected patients. VF was significantly high in ATT-coadministered patients along with a viral load of ≥1000 (p = 0.000 ). Sample Size and Characteristics . We recruited seventy-four HIV patients on 2 nd -line ART; 33 coinfected with TB were followed for at least 12 months. Conclusion . In HIV-/TB-coinfected patients, CD4 count, CD4 gain, and VF remained comparable to HIV patients with no TB infection. ATT significantly affects the treatment outcome, suggesting drug-to-drug interactions. These factors are important to revisit the therapeutic guidelines to maximize the benefit of dual therapy in resource-limited settings.